Minimum Information About a Microarray Experiment (MIAME) – Successes, Failures, Challenges - Alvis Brazma (The Scientific World Journal)
The Minimum Information About a Microarray Experiment (known as MIAME) guidelines describe information that needs to be provided to enable the interpretation of the results of a microarray-based experiment unambiguously. The MIAME guidelines were developed by the Microarray Gene Expression Data (MGED) Society. Since the MIAME position paper was published in 2001, it has been cited in the scientific literature well over a thousand times. MIAME has been replicated for many other technologies, the major data repositories are supporting MIAME, and most scientific journals have adopted MIAME guidelines as a requirement for publishing. With the advent of new-generation sequencing technology, MIAME faces new challenges. To address this, the MGED Society has proposed new guidelines, i.e., Minimum Information about a high-throughput SeQuencing Experiment (MINSEQE). Here we present analysis of the reasons for the success of MIAME, as well as discuss where it has failed, and the challenges it faces.